Early Diagnosis of Low-Risk Papillary Thyroid Cancer Results Rather in Overtreatment Than a Better Survival - Krajewska, Jolanta; Kukulska, Aleksandra; Oczko-Wojciechowska, Malgorzata; Kotecka-Blicharz, Agnieszka; Drosik-Rutowicz, Katarzyna; Haras-Gil, Malgorzata; Jarzab, Barbara; Handkiewicz-Junak, Daria (Frontiers in Endocrinology, 2020)
We are witnessing a rapid worldwide increase in the incidence of papillary thyroid carcinoma (PTC) in the last thirty years. Extensive implementation of cancer screening and wide availability of neck ultrasound or other imaging studies is the main reason responsible for this phenomenon. It resulted in a detection of a growing number of clinically asymptomatic PTCs, mainly low-risk tumors, without any beneficial impact of survival. An indolent nature of low-risk PTC, particularly papillary thyroid microcarcinoma (PTMC), and the excellent outcomes raise an ongoing discussion, regarding the adequacy of treatment applied. The question of whether PTMC is overtreated or not is currently completed by another, whether PTMC requires any treatment. Current ATA guidelines propose less extensive preoperative diagnostics and, if differentiated thyroid cancer is diagnosed, less aggressive surgical approach and limit indications for postoperative radioiodine therapy. However, in intrathyroidal PTMCs in the absence of lymph node or distant metastases, active surveillance may constitute alternative management with a low progression rate of 1-5% and without any increase in the risk of poorer outcomes related to delayed surgery in patients, in whom it was necessary. This review summarizes the current knowledge and future perspectives of active surveillance in low-risk PTC.